The effect of qualifying exercises in improving the motor range of the shoulder joint for players injured in athletics effective (discus throwing) - عذراء هادي يونس أ.د. سعاد عبد حسين (الرياضة المعاصرة)
the introduction and the importance of research the introduction said that no field of sports activity is free from the possibility of injuries, and the importance of research is the preparation of training exercises that are easy to implement with the aim of improving the motor range of the shoulder joint in the research sample, the problem of research lies in Preparation of a curriculum for therapeutic exercises as a means of rehabilitating some of the shoulder joint muscles, so the researcher considered the study of the use of rehabilitation exercises in improving the motor range of the injured in the effectiveness of discus throwing.